Analisis dan Perancangan Sistem Informasi Penjualan dan Persediaan pada PT. Xyz - Luhukay, Devyano; Kurniawan, Yohannes; Titan, Titan (Bina Nusantara University, 2013)
Based on an analysis conducted, PT XYZ may face problems on their business process since it is still executed with a non-computerized system. The purpose of this study is to improve the effectiveness and efficiency of the business processes perFormance running at the company. Besides, this study may support PT XYZ to monitor their business activities primarily from sales and inventory. The focus of the analysis and design of the inFormation systems lies in the records of beef suppies and sales transaction. A procedure and design of an integrated inFormation system in the Form a desktop application is the output of this study.